2015
DOI: 10.17723/0360-9081.78.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Archival Divides and Foreign Countries? Historians, Archivists, Information-Seeking, and Technology: Retrospect and Prospect

Abstract: Rumors of the deterioration of the historian-archivist relationship have been exaggerated. This article first traces the evolving historian-archivist bond over the last eight decades. Second, it discusses the methods scholars have employed in studying historians, namely bibliometrics, questionnaires, interviews, and a combination. Third, it describes the results and implications of those studies in three areas: locating sources, using primary and nontextual materials, and overall information-seeking and use. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
(92 reference statements)
2
4
0
Order By: Relevance
“…However, there was also consensus that professionals, even if experienced, would sometimes benefit from the advice of an archivist, while some amateurs had considerable research skills. This is similar to earlier findings [5,21].…”
Section: The Differences Between Professional and Amateur Historianssupporting
confidence: 93%
See 3 more Smart Citations
“…However, there was also consensus that professionals, even if experienced, would sometimes benefit from the advice of an archivist, while some amateurs had considerable research skills. This is similar to earlier findings [5,21].…”
Section: The Differences Between Professional and Amateur Historianssupporting
confidence: 93%
“…Huvila [4] found that the empirical approach to studying archival users, in many cases historians, has strengthened in the new millennium, coincident with an increase in digital material in archives. These studies have generally used mixed qualitative and quantitative methods, including paper-based and web-based surveys, interviews, focus groups, observations, diaries, log analysis, and experiments [5,6,7,8].…”
Section: Literature Review and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Archivaria was not cited in the library journals examined for the year 2014 (see table 3). 55 This article does consider the role information technology plays in historians' research, which supports the literature review's assertion that convergence is at least partially driven by patron access to materials.…”
Section: Journal Citation Resultssupporting
confidence: 61%